Glucan adsorption on mesoporous carbon nanoparticles effect of chain length and internal surface - Chung, Po-Wen (Langmuir : the ACS journal of surfaces and colloids, 2012)
The adsorption of cellulose-derived long-chain (longer than ten glucose repeat units on size) glucans onto carbon-based acid catalysts for hydrolysis has long been hypothesized; however, to date, there is no information on whether such adsorption can occur and how glucan chain length influences adsorption. Herein, in this manuscript, we first describe how glucan chain length influences adsorption energetics, and use this to understand the adsorption of long-chain glucans onto mesoporous carbon nanoparticles (MCN) from a concentrated acid solution, and the effect of mesoporosity on this process. Our results conclusively demonstrate that mesoporous carbon nanoparticle (MCN) materials adsorb long-chain glucans from concentrated acid hydrolyzate in amounts of up to 30% by mass (303 mg/g of MCN), in a manner that causes preferential adsorption of longer-chain glucans of up to 40 glucose repeat units and, quite unexpectedly, fast adsorption equilibration times of less than 4 min. In contrast, graphite-type carbon nanopowders (CNP) that lack internal mesoporosity adsorb glucans in amounts less than 1% by mass (7.7 mg/g of CNP), under similar conditions. This inefficiency of glucan adsorption on CNP might be attributed to the lack of internal mesoporosity, since the CNP actually possesses greater external surface area relative to MCN. A systematic study of adsorption of glucans in the series glucose to cellotetraose on MCN shows a monotonically decreasing free energy of adsorption upon increasing the glucan chain length. The free energy of adsorption decreases by at least 0.4 kcal/mol with each additional glucose unit in this series, and these energetics are consistent with CH-π interactions providing a significant energetic contribution for adsorption, similar to previous observations in glycoproteins. HPLC of hydrolyzed fragments in solution, (13)C Bloch decay NMR spectroscopy, and GPC provide material balance closure of adsorbed glucan coverages on MCN materials. The latter and MALDI-TOF-MS provide direct evidence for adsorption of long-chain glucans on the MCN surface, which have a radius of gyration larger than the pore radius of the MCN material